Implementation of creative problem-solving model with RME approach on mathematics problem-solving ability - Rahmadi, Joko; Wahyu, Yoppy; Oktari, Viscal (Universitas Hamzanwadi, 2024)
This research is motivated by the low problem-solving ability of students caused by focusing on memorizing formulas when answering questions. Innovation is needed to overcome this, one of which is through the innovative implementation of the creative problem-solving model. This study aims to see the effect of students' problem-solving skills through implementing the creative problem-solving model with the RME approach. This study uses a type of quasi-experiment with a non-equivalent control group design in class 6 on the material of building space. The population was 73 students, with a sample of 40 students consisting of 20 experimental classes and 20 control classes with simple random sampling techniques. The ice instrument used is a description test with as many as four questions. The t-test results obtained are Sig. 0.001 with a t-count of 2.387. Based on the test results that have been carried out, there is a positive influence on the implementation of the creative problem-solving model with the RME approach on students' problem-solving skills, and there is an increase in students' problem-solving skills based on the pretest-posttest value of 31.6.